2015
DOI: 10.1111/jth.13001
|View full text |Cite
|
Sign up to set email alerts
|

The important role of von Willebrand factor in platelet‐derived FVIII gene therapy for murine hemophilia A in the presence of inhibitory antibodies

Abstract: Background Our previous studies have demonstrated that targeting FVIII expression to platelets results in FVIII storage together with VWF in platelet α-granules and that platelet-derived FVIII (2bF8) corrects the murine hemophilia A phenotype even in the presence of high-titer anti-FVIII inhibitory antibodies (inhibitors). Objective To explore how VWF impacts platelet gene therapy of hemophilia A with inhibitors. Methods 2bF8 transgenic mice in the F8−/− background (2bF8tg+/−F8−/−) with varying VWF phenoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 52 publications
(77 reference statements)
1
16
0
Order By: Relevance
“…26 The interaction between VWF and FVIII is critical in maintaining the clinical efficacy of platelet-derived FVIII gene therapy in HA mice in the presence of inhibitors. 27 How VWF affects FVIII immune responses in HA with a setting of preexisting anti-FVIII immunity is still uncertain and is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…26 The interaction between VWF and FVIII is critical in maintaining the clinical efficacy of platelet-derived FVIII gene therapy in HA mice in the presence of inhibitors. 27 How VWF affects FVIII immune responses in HA with a setting of preexisting anti-FVIII immunity is still uncertain and is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been demonstrated that targeting FVIII expression to platelets results in FVIII storage together with VWF in platelet a-granules and corrects the murine hemophilia A phenotype even in the presence of high-titer anti-FVIII inhibitory antibodies (inhibitors). 47 …”
mentioning
confidence: 99%
“…In a murine model of haemophilia, the presence of pre‐existing FVIII inhibitory antibodies did not negate the therapeutic 2bF8 engraftment when efficient pre‐conditioning regimens had been employed . In the absence of VWF, however, levels of platelet‐derived FVIII were significantly decreased and its therapeutic efficacy was aborted in the presence of inhibitors .…”
Section: Targeting Cells That Synthesize Vwfmentioning
confidence: 96%